Thrombolysis in Acute Ischemic Stroke after Idarucizumab for Dabigatran Etexilate Reversal in Elderly: A Case Report - Baule, Antonio (J Vasc Interv Neurol, 2018)
INTRODUCTION: Dabigatran is one of the nonvitamin K antagonist oral anticoagulants. Thrombolytic treatment with intravenous recombinant tissue plasminogen activator is contraindicated in patients taking a DOAC. Idarucizumab was recently approved for dabigatran-activity reversing in severe bleeding, emergency surgery, or urgent procedures, but many attempts have been made to use idarucizumab in patients presenting with acute ischemic stroke in order to be eligible for thrombolysis. CASE: Our patient was an 89-year-old woman with severe aphasia who was treated with dabigatran for nonvalvular atrial fibrillation. She received an infusion of idarucizumab followed by thrombolytic therapy, with complete remission of symptoms after 24 hours. DISCUSSION: Idarucizumab is a safe option for patients with acute ischemic stroke treated with dabigatran; otherwise eligibles for thrombolysis, even in very old people like our patient.